Pengaruh Campuran Pasir dan Serat Aren pada Kailan (Brassica oleraceae) dengan Hidroponik Substrat - Samanhudi Samanhudi; Dwi Hardjoko; Riandy Adhitya (Agrosains : Jurnal Penelitian Agronomi, 2014)
Wood fiber waste of arenga produced from starch palm industry. It is not handled properly so that could be potentially cause problems for the surrounding community. Wood fiber waste of arenga is potentially used as a medium for hydroponics. The waste can be utilized to get a new composition of hydroponic media. This study aims to determine the effect of a mixture of sand with arenga fiber waste. This research was carried out by using a mixture of sand and arenga wood fiber waste as a medium. This is an experimental study using a completely randomized design. This study aims to determine the effect of a mixture of sand and arenga fiber waste for kailan growth. The results showed that the mixture of sand and arenga wood fiber waste has no effect on kailan growth. The combination of mixtures of sand and arenga fiber waste showed no interaction. Observations on plants such as plant height, number of leaves, leaf greenness levels, the fresh weight of crop stover and stover dry weight of the plant, showed a row of the highest results in the media mix washed sand, washed sand and rice husk